Holocentric Karyotype Evolution in Rhynchospora Is Marked by Intense Numerical, Structural, and Genome Size Changes - Burchardt, Paula; Buddenhagen, Christopher E.; Gaeta, Marcos L.; Souza, Murilo D.; Marques, André; Vanzela, André L. L. (Frontiers in Plant Science, 2020)
Cyperaceae is a family of Monocotyledons comprised of species with holocentric chromosomes that are associated with intense dysploidy and polyploidy events. Within this family the genus Rhynchospora has recently become the focus of several studies that characterize the organization of the holocentric karyotype and genome structures. To broaden our understanding of genome evolution in this genus, representatives of Rhynchospora were studied to contrast chromosome features, C-CMA/DAPI band distribution and genome sizes. Here, we carried out a comparative analysis for 35 taxa of Rhynchospora, and generated new genome size estimates for 20 taxa. The DNA 2C-values varied up to 22-fold, from 2C = 0.51 pg to 11.32 pg, and chromosome numbers ranged from 2n = 4 to 61. At least 37% of our sampling exhibited 2n different from the basic number x = 5, and chromosome rearrangements were also observed. A large variation in C-CMA/DAPI band accumulation and distribution was observed as well. We show that genome variation in Rhynchospora is much larger than previously reported. Phylogenetic analysis showed that most taxa were grouped in clades corresponding to previously described taxonomic sections. Basic chromosome numbers are the same within every section, however, changes appeared in all the clades. Ancestral chromosome number reconstruction revealed n = 5 as the most likely ancestral complements, but n = 10 appears as a new possibility. Chromosome evolution models point to polyploidy as the major driver of chromosome evolution in Rhynchospora, followed by dysploidy. A negative correlation between chromosome size and diploid number open the discussion for holokinetic drive-based genome evolution. This study explores relationships between karyotype differentiation and genome size variation in Rhynchospora, and contrasts it against the phylogeny of this holocentric group.